Reduction of shunt current in buffer-free IrMn based spin-valve structures - Kocaman, B.; Akdogan, N. (Elsevier Science Bv, 2018)
The presence of thick buffer layers in magnetic sensor devices decreases sensor sensitivity due to shunt currents. With this motivation, we produced IrMn-based spin-valve multilayers without using buffer layer. We also studied the effects of post-annealing and IrMn thickness on exchange bias field (H-EB) and blocking temperature (TB) of the system. Magnetization measurements indicate that both HEB and TB values are significantly enhanced with post-annealing of IrMn layer. In addition, we report that IrMn thickness of the system strongly influences the magnetization and transport characteristics of the spin-valve structures. We found that the minimum thickness of IrMn layer is 6 nm in order to achieve the lowest shunt current and high blocking temperature (>300 K). We also investigated the training of exchange bias to check the long-term durability of IrMn-based spin-valve structures for device applications. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Giant Magnetoresistance; Exchange Bias; Magnetic-Properties; Anisotropy; Temperature; Layer